Effects of latitude and conspecific plant density on insect leaf herbivory in oak saplings and seedlings. Issue 1 (14th January 2021) - Moreira, Xoaquín; Abdala‐Roberts, Luis; De Frenne, Pieter; Galmán, Andrea; Gaytán, Álvaro; Jaatinen, Raimo; Lago‐Núñez, Beatriz; Meeussen, Camille; Pulkkinen, Pertti; Rasmussen, Pil U.; Ten Hoopen, Jan P.J.G.; Timmermans, Bart G.H.; et al.
Abstract : Premise: Abiotic factors and plant species traits have been shown to drive latitudinal gradients in herbivory, and yet, population‐level factors have been largely overlooked within this context. One such factor is plant density, which may influence the strength of herbivory and may vary with latitude. Methods: We measured insect herbivory and conspecific plant density (CPD) of oak ( Quercus robur ) seedlings and saplings along a 17° latitudinal gradient (2700 km) to test whether herbivory exhibited a latitudinal gradient, whether herbivory was associated with CPD, and whether such an association changed with latitude. Results: We found a positive but saturating association between latitude and leaf herbivory. Furthermore, we found no significant relationship between CPD and herbivory, and such lack of density effects remained consistent throughout the sampled latitudinal gradient. Conclusions: Despite the apparently negligible influence of plant density on herbivory for Q. robur, further research with other plant taxa and in different types of plant communities are needed to investigate density‐dependent processes shaping geographical variation in plant–herbivore interactions.